2012
DOI: 10.1103/physrevb.86.035149
|View full text |Cite
|
Sign up to set email alerts
|

Product vacua with boundary states

Abstract: We introduce a family of quantum spin chains with nearest-neighbor interactions that can serve to clarify and refine the classification of gapped quantum phases of such systems. The gapped ground states of these models can be described as a product vacuum with a finite number of particles bound to the edges. The numbers of particles, nL and nR, that can bind to the left and right edges of the finite chains serve as indices of the particular phase a model belongs to. All these ground states, which we call Produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The goal of this work is to determine for each combination of unit inward pointing normal m ∈ R d and parameters λ ∈ (0, ∞) d whether the gap γ(H D ) vanishes or not and to find explicit bounds for the gap whenever possible. The case d = 1 was treated in [1] where it was shown that model is gapless if λ = 1 and gapped otherwise. Special for the case d = 1 is that the ground state space for the half-infinite chain [1, ∞) ⊂ Z is two-dimensional if m log λ < 0 and one-dimensional if m log λ ≥ 0.…”
Section: Definition Of the Model And Main Resultsmentioning
confidence: 99%
“…The goal of this work is to determine for each combination of unit inward pointing normal m ∈ R d and parameters λ ∈ (0, ∞) d whether the gap γ(H D ) vanishes or not and to find explicit bounds for the gap whenever possible. The case d = 1 was treated in [1] where it was shown that model is gapless if λ = 1 and gapped otherwise. Special for the case d = 1 is that the ground state space for the half-infinite chain [1, ∞) ⊂ Z is two-dimensional if m log λ < 0 and one-dimensional if m log λ ≥ 0.…”
Section: Definition Of the Model And Main Resultsmentioning
confidence: 99%
“…Bacterial Strains, Phages, and Culture Conditions-Genetic experiments were carried out in E. coli strain SG20781 (32), MC4100 (33), W3110, or MG1655 (34). The deletion/replacement of the lon gene by a Kan R cassette was carried out as described (35) using pKD4 as the DNA template (36).…”
Section: Methodsmentioning
confidence: 99%
“…This is precisely the same structure occurring in, e.g., product vacua with boundary states [31,32] , so simplifying P E also yields insight into the structure of RG fixed points. not have any fixed points.…”
Section: Adding Decaymentioning
confidence: 84%